2002
DOI: 10.1200/jco.20.3.688
|View full text |Cite
|
Sign up to set email alerts
|

Lymphatic Mapping and Sentinel Node Identification in Patients With Cervix Cancer Undergoing Radical Hysterectomy and Pelvic Lymphadenectomy

Abstract: Preoperative lymphoscintigraphy and intraoperative lymphatic mapping were highly successful at identifying sentinel nodes in patients undergoing radical hysterectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
93
2
13

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(116 citation statements)
references
References 13 publications
8
93
2
13
Order By: Relevance
“…Obturator lymph nodes are most likely to be involved in metastatic disease, followed by external iliac, common iliac, and parametrial lymph nodes [51]. Skip metastases to paraaortic lymph nodes are rarely seen and account for Ͻ1% of cases [52,53]. The SLN in cervical cancer is situated in the obturator region in 43% of cases and in the external iliac region in 45%-84% of cases [54,55].…”
Section: Lymphatic Drainage Of the Female Genital Tractmentioning
confidence: 99%
“…Obturator lymph nodes are most likely to be involved in metastatic disease, followed by external iliac, common iliac, and parametrial lymph nodes [51]. Skip metastases to paraaortic lymph nodes are rarely seen and account for Ͻ1% of cases [52,53]. The SLN in cervical cancer is situated in the obturator region in 43% of cases and in the external iliac region in 45%-84% of cases [54,55].…”
Section: Lymphatic Drainage Of the Female Genital Tractmentioning
confidence: 99%
“…Also promising is the use of hypoxia tracers in PET imaging [56,57]. Because hypoxia is an important prognostic factor in cervical cancers, the use of 18 F-FMISO ( 18 F-fluoromisonidazole) or 60 Cu-ATSM [ 60 Cu-diacetyl-bis (N 4 -metylthiosemicarbazone)] as hypoxia tracers may give the clinicians determining information on tumour components [58]. These tracers also may be particularly useful for the initial assessment of tumour responsiveness to treatment, knowing that hypoxic cells are rather resistant to radiotherapy and chemotherapy [59].…”
Section: Perspectivesmentioning
confidence: 99%
“…These tracers also may be particularly useful for the initial assessment of tumour responsiveness to treatment, knowing that hypoxic cells are rather resistant to radiotherapy and chemotherapy [59]. On the other hand, the validation of the sentinel node concept in early stage cervical cancers along with the molecular analysis of the sentinel lymph nodes (SLN) may grant new perspectives for the selective evaluation of regional nodal status [60,61,62]. Accordingly, most women with early stage disease and negative SLN will be spared the morbidity resulting from unnecessary complete lymph node dissections.…”
Section: Perspectivesmentioning
confidence: 99%
“…This situation is clearly different from other viscera, such as the lung and oesophagus [20], mammary gland [26] and stomach [16,23]. Thus, application of sentinel node biopsy for carcinomas of the uterus [11,12] appeared to precede descriptions of normal adult anatomy of the lymphatic drainage routes. Likewise, to our knowledge, no or few studies have demonstrated the LVs around the normal uterus using D2-40 immunohistochemistry, in contrast to the extensive accumulation of knowledge of D2-40-positive LVs in other normal viscera (e.g., oesophagus [34], prostate [6], kidney [9] and others [7]).…”
Section: Introductionmentioning
confidence: 99%